Pelizaeus-Merzbacher-Like Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A family with X-linked inheritance and Pelizaeus-Merzbacher-like disease (PMLD), PMD without the proteolipid protein (PLP) mutation, studied at the UMDNJ-Robert Wood Johnson Medicial School, New Brunswick, NJ, had a new locus on Xq chromosome, more than 10 cM away from PLP.